OCTOPUS EXPORT PERFORMANCE ANALYSIS (Octopus sp) PT AGRITA BEST SEAFOOD - Muh. Karim; Tri Novita (Universitas Trilogi, 2026)
The fisheries sector makes a substantial contribution to national economic development, notably through the export of octopus (Octopus sp.) commodities. PT Agrita Best Seafood serves as a major exporter of frozen octopus to the United States, the European Union, and Japan. This study examines the export performance and national competitiveness of Indonesian octopus enterprises through the application of Analytic Hierarchy Process (AHP), Revealed Comparative Advantage (RCA), and Constant Market Share (CMS) methodologies. Findings from the AHP indicate that export demand is the principal factor, with a weight of 0.245. The RCA index ranks Indonesia as the world’s second-largest exporter of frozen octopus, with a score of 6.46. Results from the CMS analysis demonstrate positive contributions from both composition and competitiveness effects. To further enhance export performance, governmental policy interventions are recommended, including quality assurance, streamlined licensing procedures, support for small and medium-sized enterprises, market expansion, and improved data transparency. Moreover, collaborative engagement between governmental bodies and industry stakeholders is vital to sustainably reinforce the international competitiveness of Indonesian octopus commodities.